Student Perception Of Learning Modalities In Physiology In Integrated Curriculum - Sadaf Fatima; Arshia Samin Naqvi; Syed Tousif Ahmed (ziauddin University, 2024)
Background: Currently most of the medical schools are incorporating innovative medical curricula in their bachelor programs. Most of the institutions are moving towards a more student centered approach to learning and assessment. Physiology being one of the mandatory basic science disciplines is also experiencing these changes. Student learning is always related to the teaching methodologies being used. Student's perception of the various teaching methodologies is useful in improving the quality of learning in medical education and to evaluate the student perception of different learning modalities in physiology in an integrated curriculum. Methods: Study was conducted on 100 medical students of 1st and 2nd Year. Participating students were explained the purpose of study. Based on the teaching methods practiced in the department of Physiology at Ziauddin Medical College, a survey questionnaire was prepared and given to the participants. The questionnaire consisted of questions enquiring about the preference of different learning/ teaching methods and the reason for the preference. Results: Majority of the students of 1st and 2nd year MBBS selected Problem based learning (PBL) 48% lecture 40% and small group session 7 % and other teaching method 5%. Conclusion: Problem based learning was found to be the preferred learning modality to study physiology and lecture was the most helpful method in preparing for exams. Key Words: Perception, Physiology, Teaching Tools, Learning, Integrated Curriculum